PENERAPAN MODEL PEMBELAJARAN STEM UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA DI SEKOLAH DASAR - Hardika Emil; Yenni Fitra Surya; Nurhaswinda; Mufarizuddin; Putri Hana Pebriana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the low critical thinking skills of students in class IV-B, particularly in Mathematics learning. The aim of this study is to improve the critical thinking abilities of the fourth-grade students at UPT SDN 001 Airitiris. The observed deficiency in critical thinking skills can be addressed through the application of the STEM learning model (Science, Technology, Engineering, and Mathematics). This study is classified as classroom action research, conducted over two cycles, with each cycle comprising two meetings. The subjects of this research include the IV-B class teacher, peers, and 21 students, while the object focuses on utilizing the STEM learning model to enhance students' critical thinking skills. The research instruments consist of observation sheets for both teacher and student activities, test sheets, and documentation sheets. The data analysis techniques employed are both qualitative and quantitative. Based on the results of the research conducted over two cycles, in the first cycle during the first meeting, the students' critical thinking skills were categorized as low at 38%, and in the second meeting, they remained in the low category at 43%. In the second cycle, the first meeting showed that students' critical thinking skills had improved to a moderate level, and in the second meeting, they reached a critical level at 86%. The findings of this study indicate that the implementation of the STEM learning model can effectively enhance the critical thinking skills of IV-B students at UPT SDN 001 Airitiris.